Failure of iodine uptake in microscopic pulmonary metastases after recombinant human thyroid-stimulating hormone stimulation - Lawhn-Heath, Courtney; Flavell, Robert; Chuang, Eunice; Liu, Chienying (World Journal of Nuclear Medicine, 2020)
Elevated thyroid stimulating hormone (TSH) is required when preparing for radioactive iodine therapy in patients with differentiated thyroid cancer. Recombinant human TSH (rhTSH: Thyrogen; Genzyme Corporation, Cambridge, MA) avoids hypothyroidism and has been commonly used in place of thyroid hormone withdrawal (THW) in this process. We describe a 31-year-old woman with sclerosing variant of papillary thyroid cancer with multiple lymph node metastases and elevated postoperative thyroglobulin suggesting the presence of distant metastases, who was found to have miliary pulmonary metastases on the posttherapy I-131 scan after THW, but not visible on the post therapy scan after rhTSH preparation.
Keywords: Hypothyroidism; radioiodine; recombinant human thyroid-stimulating hormone; thyrogen; thyroid cancer